PENGARUH BRAND IMAGE DAN PRICE TERHADAP PURCHASE INTENTION HP OPPO DI TOKO PUSPITA CELL PAMEKASAN - Fathorrahman Fathorrahman; Citra Larasathi Surya (Assyarikah: Journal of Islamic Economic Business, 2021)
The purpose of this study was to determine the effect of Brand Image and Price Simultaneously and Partially on Purchase Intention Oppo cellphones at the Puspita Cell Pamekasan Shop. The object of this research is consumers who buy Oppo Hp products at the Puspita Cell Pamekasan Shop. The sample of this study used a sample of 100 respondents using random sampling techniques. Data collection is based on distributing questionnaires. The research model used is by using multiple linear regression. The results of the study was Brand Image and Price simultaneously have a positive and significant effect on Purchase Intention and Brand Image and Price partially have a positive and significant effect on Purchase Intention.